Limitations of HLH‐2004 criteria in distinguishing malignancy‐associated hemophagocytic lymphohistiocytosis. Issue 12 (1st October 2018) - Gurunathan, Arun; Boucher, Alexander A.; Mark, Melissa; Prus, Kristina M.; O'Brien, Maureen M.; Breese, Erin H.; Mizukawa, Benjamin E.; Absalon, Michael J.; Nelson, Adam S.; Jordan, Michael B.; Grimley, Michael S.; Lorsbach, Robert B.; et al.
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is characterized by dysregulated immune activation.  Primary HLH involves hereditary deficits in cytotoxic lymphocytes while secondary HLH is triggered by extrinsic factors. The HLH‐2004 criteria are widely used for clinical diagnosis, yet their specificity for HLH or their ability to differentiate primary from secondary disease is unclear, potentially leading to inappropriate treatment. We describe several cases where fulfillment of HLH‐2004 criteria obscured the diagnoses of underlying malignancies and delayed curative management. These issues are remedied without waiting for genetic testing results through an alternative diagnostic approach using flow cytometry–based immunologic assays and a thorough investigation for malignancy.